Formulation, Evaluation, and Optimization of Budesonide Pulsincap Drug Delivery System for Chronotherapy of Asthma - Ande, P Pratyusha (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The present study was aimed to design and optimize colon-targeted drug delivery system of budesonide for the treatment of asthma. Materials and Methods: The system consists of formaldehyde-treated insoluble hard gelatin capsule body filled with budesonide-sustained release granules prepared with different polymers of HPMCK4M, Eudragit L100, and ethyl cellulose 20cps. A response surface methodology based on central composite design was employed to investigate the influence of the amount of HPMCK15M (hydrogel plug) and KCl (osmogen) on the lag time and percent drug release. Results and Discussion: The optimized formulation (P9) containing budesonide-sustained release granules of 120 mg, hydrogel plug of 100 mg, and osmogen of 80 mg, and formulation was prepared according to software determined levels. Both hydrogel plug and osmogen had a significant influence on the lag time and percent drug release. In vivo X-ray imaging study confirmed that the coated capsules dissolved at the targeted colon region. Conclusion: The present pulsincap formulation was effective in providing colon-targeted drug release after predetermined lag time.